UM MÉTODO MAIS EFICIENTE DE ISOLAMENTO DO LAPACHOL DIRETAMENTE DA MATRIZ VEGETAL DO IPÊ - Douglas Chaves de Alcantara Pinto; Robson Corrêa da Silva; Luana da Silva Magalhães Forezi; Vitor Francisco Ferreira; Fernando de Carvalho da Silva (Química Nova, 2024)
Lapachol, a naphthoquinone discovered in 1858, is a natural product with a broad spectrum of therapeutic activities, along with its derivatives and analogues. Initially found in several species of the Bignoniaceae family, lapachol can also be found in other families. Lapachol arouses great interest and knowledge due to its crucial role in medicinal chemistry, playing an important role in the rational planning of research in search of bioactive substances with pharmacological action, whether as a source of raw material or helping directly or indirectly. This work aims to describe a new methodology for extracting lapachol, which differs from the conventional acid-base method, providing a highly efficient, simple and easy-to-apply process.